Hyperglycemia, Assessed by HbA1c, and Future Risk of Venous Thromboembolism - The Tromsø Study - Lerstad, Gunhild; Brodin, Ellen Elisabeth; Enga, Kristin; Jorde, Rolf; Schirmer, Henrik; Njølstad, Inger; Svartberg, Johan; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (Journal of Thrombosis and Haemostasis, 2014)
This is the accepted manuscript version. Published version, with slightly altered title, is available in Journal of Thrombosis and Haemostasis 12(2014) Background: Glycated hemoglobin (HbA1c), a marker of average plasma glucose during the last 8-12 weeks, is associated with future risk of cardiovascular disease (CVD) and all-cause mortality. Objectives: To examine the association between hyperglycemia, assessed by HbA1c, and future risk of VTE in a population based cohort. Methods: HbA1c was measured in 16 156 unique subjects (25-87 years) who participated in one or more surveys of the Tromsø study (Tromsø 4; 1994-95, Tromsø 5; 2001-2, and Tromsø 6; 2007-8). All subjects were followed, and incident VTE events were recorded through December 31, 2010. Results: There were 333 validated first VTE events, of which 137 were unprovoked, during a median follow-up of 7.1 years. HbA1c was not associated with future risk of VTE in analysis treating HbA1c as a continuous variable, or in categorized analyses. The risk of VTE increased by 5% per 1 SD (0.7%) increase in HbA1c (multivariableadjusted HR 1.05; 95% CI 0.97-1.14), and subjects with HbA1c ≥ 6.5% had 27% higher risk compared to those with HbA1c below 5.7% (multivariable-adjusted HR 1.27; 95% CI 0.72-2.26). There was no significant linear trend for increased risk of VTE across categories of HbA1c (p=0.27). Conclusions: Serum levels of HbA1c were not associated with future risk of VTE in multivariable analysis. Our findings suggest that hyperglycemia does not play an important role in the pathogenesis of VTE